Aldous Huxley: the unstable self, consciousness and the 'ground of being'. Issue 9 (1st September 2020) - Woodberry, Imogen
ABSTRACT: This article explores Aldous Huxley's understanding of the self, reading him as both participant in the early century modernist quest to explore the fractured nature of subjectivity, and resistor of that quest's aesthetic implications. Huxley's authorial focus on externality while his peers probed the interior, I argue, bears a passing resemblance to the aesthetics of high modernist figures such as Wyndham Lewis and T.E. Hulme, but speaks to an optimistic antidote to their pessimism about the limits of human capability. Tracing his tonal development from sardonic and satirical in the 1920s to affirmative, didactic and therapeutic in run up to World War Two, I discuss his humanist aims in the context of an enduring anti-humanist inflection. At the same time, I show that inflection to have involved a destabilising of selfhood for the purpose of rebuilding, rather than the more usual modernist anti-humanist expression of its limitations. What were, in some ways, the irrational and deviant systems of psychic research, Theosophy, Western mysticism and Eastern religion provided Huxley with a model for thinking about how the self might be conceived of as a potentially complete and rational agent – albeit with a reconstructed consciousness that was broadened, expanded and re-located.